RIGID BODY IN THE THREE DIMENSIONAL RIGGING MODEL FOR CAR ANIMATION IN A BUMPY ROAD - Aryanto, Salam (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2020)
The development of animation technology is currently very rapid, but to animate a three-dimensional object beforehand must be done by preparing the framework manually. Also in the real world, when two objects collide, they do not penetrate each other. When a collision occurs, the interaction force will change the original state of two objects, such as position, trajectory, and direction. The purpose of this study focuses on the rigid body in a three dimensional rigging model arrangement for car animation scenarios on a bumpy road. This approach focuses on reducing manual movement by animators when animating three-dimensional car models. The result is to make a car animation on a bumpy road well, then the arrangement of the framework on the car has a mass = 1946 kg and gravity = -981.001 cm / s2. As well as knowing the results of the animated motion of the car on a bumpy road with a tolerance of distance between the car's wheels and the trajectory of 4.44 cm without applying a rigid body to the arrangement of the car's frame. While the motion animation of the car on a bumpy road with good results where the tolerance of the distance between the car wheels and the track is 0.045 cm after applying a rigid body to the arrangement of the car's frame.